RELIGION AND HARRITAGE: THE ISLAMIC MANUSCRIPT OF THE QURAN BY ABDURRAHMAN HUSIN FALLUGAH (W.2010) - Faizal Amin (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
This article is extracted from the philological-codicological research on the Mushaf Al-Qur’an (codex or collection of sheets of the Qur’an, hereafter referred to as the mushaf) manuscript in West Kalimantan, especially the collection of Abdurrahman Husin Fallugah (hereafter referred to as AHF). Overall, the Qur’an manuscript collection of AHF is 20 copies, consisting of 15 mushaf in complete condition and six other mushaf which are not complete. The study only focused on 15 mushaf which are intact and complete. The findings of this research showed that: first, judging from its origins, not all of the mushaf manuscript collection of AHF came from West Kalimantan. In addition to West Kalimantan, the 15 complete mushaf also came from Aceh and Central Java. The initiators and supporters of the writing of the manuscript were probably members of a royal family since the Qur’an manuscripts in West Kalimantan were originally obtained from a royal family. Second, the condition of 15 mushaf collection of AHF is generally quite well preserved despite some physical damage especially on the edges of the sheet of paper. If seen from kind of material used, the mushaf collection of AHF were made from different materials, some made from the local paper, some made from European paper and some also made from animal skins. Meanwhile, the collection of the 15 manuscripts is complete; each consists of 30 juz (parts) covering 114 surah. The oldest Mushaf manuscript is coded AHF-06 made by H.M. Said al-Katib in 1067 AH or 1657 AD, while the latest manuscript coded AHF-02 written by H. Sarqawiy in 1243 AH or 1828 AD.